Harnessing the Potential of Nodule Endophytic Bacteria to Improve Soybean Growth Under Saline Conditions - Humaira Islam; Mohsin Tariq; Kashif Sattar; Tahira Yasmeen; Muhammad Abdul Rehman Rashid (Current Microbiology, 2026)

Integrated spatial analysis and Gaussian dispersion modelling of airborne particulate matter from rice processing mill hubs in rural Bangladesh and associated public health risks - Rubaiatul Islam Zerin; Md. Kamrul Hossain; Humaira Rashid; Sababa Tasnim; Md. Julfikar Ali; Md. Mizanur Rahman; Mohd. Maniruzzaman; Rafiquel Islam (Environmental Science and Pollution Research, 2026)

Spatial Distribution and AirQ + -Based Health Risk Analysis of Particulate Matter in Bangladesh’s Industrial Hubs - Md. Kamrul Hossain; Rubaiatul Islam Zerin; Humaira Rashid; Umma Suraiya Parvin Kakon; Mst. Sadia Siddika Trina; Laila Anjum Eva; Shahin Ali; Mohammad Omar Faruk Molla; Md. Saikoth Jahan; Md. Assraf Seddiky; Sazal Kumar; Mohd. Maniruzzaman; et al. (Water, Air, & Soil Pollution, 2026)
Rapid urbanisation and population growth in Bangladesh have intensified ambient particulate matter (PM 2.5 and PM 10 ) pollution, posing critical threats to public health. This study assessed PM concentration in three major industrial cities, Dhaka, Narayanganj, and Gazipur. PM concentrations were measured using an Air Particle Counter and an optimised air-quality sensor. PM measurements were conducted at 138 sampling points across Dhaka, Narayanganj, and Gazipur in October 2023, a climatologically stable late-autumn period, providing a reliable baseline for assessing ambient PM levels. Long-term chronic and acute diseases were quantified using the WHO AirQ + tool, including acute lower respiratory infection (ALRI) in children, chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), stroke, and lung cancer (LC) in adults. The study revealed that the average PM 2.5 concentrations of 74.04, 56.70, and 63.99 µg/m 3 exceeded WHO standards in three cities and exceeded BD standards only in Dhaka, while PM 10 levels exceeded only WHO standards. A strong correlation was observed between PM 2.5 and PM 10 . Meteorological analysis indicated that wind speed and direction were key dispersion drivers, whereas temperature and humidity showed weak inverse exponential relationships with PM levels. Hazard Quotient (HQ) derivation revealed significant non-cancer health risks, with values exceeding unity. In contrast, PM 2.5 significantly affected ALRI mortality among children, with rates of 0.52, 0.44, and 0.49 per 100,000 in Dhaka, Narayanganj, and Gazipur, respectively. In adults, stroke was the leading PM 2.5 -related cause of death, with rates of 9.87, 9.13, and 9.63 per 100,000 in these cities. IHD deaths were also high, while LC and COPD mortality ranged from low to moderate. The study underscores the substantial public health implications of persistent PM pollution across Bangladesh’s industrial cities and reinforces the urgency of implementing coherent regulatory interventions. To strengthen the precision of exposure assessments and support more robust evidence-based policymaking, future investigations should incorporate multi-seasonal sampling, extended temporal monitoring, and broader spatial representation across diverse industrial zones.

Changing water sources and extraction methods in Bangladesh: Challenges, consequences, and sustainable solutions - Md. Jakariya; Mohammad Moshiur Rahman; Lamia Mahzabin; Adrita Chowdhury; Humaira Adiba; Md. Sajadul Alam; Mohammed Fahim Murshed; Christian Sonne; Damià Barceló; Junxu Chen; Md. Aminul Islam; Prosun Bhattacharya (Groundwater for Sustainable Development, 2024)

Developing a safe water atlas for sustainable drinking water supply in Sonargaon Upazila, Bangladesh - Md. Jakariya; Mohammad Moshiur Rahman; Lamia Mahzabin; Adrita Chowdhury; Humaira Adiba; M. Murshed Alam; Anika Islam; Tazin Mahmud Ashik; Turasa Nahla; Ibrahim Abdullah Mannan; Rifah Nanzibah; Khandaker Maisha Jahan; et al. (Groundwater for Sustainable Development, 2024)

Mitigation of the Deleterious Effect of Heavy Metals on the Conformational Stability of Ubiquitin through Osmoprotectants - Khadega Khamis Moh Alazoumi; Pradakshina Sharma; Asimul Islam; Humaira Farooqi (Cell Biochemistry and Biophysics, 2023)

Abundance, characteristics, and ecological risks of microplastics in the riverbed sediments around Dhaka city - Md. Saiful Islam; Md. Rezaul Karim; Md Tanvirul Islam; Humaira Tasnim Oishi; Zarin Tasnim; Harinarayan Das; A. H. M. Enamul Kabir; Masahiko Sekine (Science of The Total Environment, 2023)

Infiltration in vegetated soil: empirical modeling and sensitivity analysis - Md. Enayet Chowdhury; Mohammad Shariful Islam; Tahsina Alam; Sagar Barua; Md. Safin Shahriar; Humaira Anisa (Modeling Earth Systems and Environment, 2021)